A study of the phase transitions, electronic structures and thermodynamic properties of Mg2X (X = Ge, Si and Sn) under high pressure - Guezlanea, M. (H. : ĐHQGHN, 2017)
In this work, we theoretically investigate phase transitions, electronic structures and thermodynamic properties of Mg2X(X¼Ge, Si and Sn) under high pressures. To reach this goal, the total energy has been calculated by using the full-potential linearized augmented plane wave (FP-LAPW) method with generalized gradient approximation (GGA), local density approximation (LDA) and EngeleVosko approximation (EV-GGA), which are based on the exchange-correlation energy optimization. The fully relaxed structure parameters of Mg2X compounds are in good agreement with the available experi-mental data. Our results demonstrate that the Mg2X compounds undergo two pressure-induced phase transitions. The first one is from the cubic antifluorite (Fm3m) structure to the orthorhombic anticotunnite (Pnma) structure in the pressure range of 3.77e8.78 GPa (GGA) and 4.88e8.16 GPa (LDA). The second transition is from the orthorhombic anticotunnite structure to the hexagonal Ni2In-type (P63mmc) structure in the pressure range of 10.41e29.77 GPa (GGA) and 8.89e63.45 GPa (LDA). All the structural parameters of the high pressure phases are analyzed in detail. Only a small difference in the structural parameters is observed at high pressures between the calculated and experimental results. The electronic and thermodynamic properties are also analyzed and discussed. The estab-lishment of the metallic state of the Mg2X(X¼Ge, Si and Sn) compounds at high pressure is confirmed.